2017
DOI: 10.1155/2017/1239404
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Integrated Health Management Intervention on Overweight and Obesity

Abstract: Overweight or obese adults aged 20~55 years and living in Beijing more than one year were randomly divided into different management groups. A one-year integrated health management intervention was applied in the health management groups. The physical indicators and metabolic indicators changed after one-year intervention on the overweight and obese adults. The annual reduction of the physical indicators was significant in all groups (p < 0.05) except the weight loss in the placebo + general management group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Height was measured to the nearest 0.5 cm using a stadiometer, with the participant not wearing footwear. Overweight (24 kg/m 2 ≤ BMI <28 kg/m 2 ) and obesity (BMI ≥ 28 kg/m 2 ) were identified using standard Chinese-specific BMI cutoff values ( Jin et al, 2013 ; Yang et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Height was measured to the nearest 0.5 cm using a stadiometer, with the participant not wearing footwear. Overweight (24 kg/m 2 ≤ BMI <28 kg/m 2 ) and obesity (BMI ≥ 28 kg/m 2 ) were identified using standard Chinese-specific BMI cutoff values ( Jin et al, 2013 ; Yang et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Te weight loss results in reduced blood pressure, improved lipids, and reduced diabetes incidence. Hence, it becomes imperative to manage and treat obesity in its nascent stage [68]. It is important to know that the cost of obesity increases not only due to comorbidities but also due to absenteeism, disability, early death, and other factors attributed to obesity.…”
Section: Need For Treatmentmentioning
confidence: 99%
“…Different diet and exercise management methods play an important role in the intervention of simple obesity. [15][16][17][18] Nowadays, the combination of online and offline health education has been realized through multimedia education, telephone interviews, offline lectures, and other ways. Obesity related health education content includes the cognition of disease, diet structure, physical exercise, regular work and rest, psychological intervention, and so on.…”
Section: Description and Function Of Interventionmentioning
confidence: 99%
“…Relevant studies have confirmed that multimode health education can be explained through multiple channels and appropriate education methods, it can be selected for different individuals to improve the cooperation between patients and medical staff. Different diet and exercise management methods play an important role in the intervention of simple obesity [15–18] …”
Section: Introductionmentioning
confidence: 99%